2022
DOI: 10.1002/jhet.4587
|View full text |Cite
|
Sign up to set email alerts
|

Advances in synthesis and biological activities of benzotriazole analogues: A micro review

Abstract: Although the first synthesis of benzotriazole was performed in the 19th century still new methods for their preparation have developed. In this micro review authors focus mostly on the various synthetic strategies developed so far to synthesize benzotriazole and its derivatives by different strategies, such as metal‐free, metal‐assisted [3 + 2] cycloaddition reactions, cyclocondensations, flow methods, heterocyclizations, and so forth. This micro review combines recent (2005–2022 till date) information on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…1d, 129 In addition to the versatile synthetic utilities of N-acyl benzotriazoles, this scaffold possesses some notable bioactivities and explored in medicinal chemistry. 130 Structure of some biologically potent N-acylbenzotriazole is depicted in Figure 3.…”
Section: Pharmacological Applications Of N-acyl Benzotriazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…1d, 129 In addition to the versatile synthetic utilities of N-acyl benzotriazoles, this scaffold possesses some notable bioactivities and explored in medicinal chemistry. 130 Structure of some biologically potent N-acylbenzotriazole is depicted in Figure 3.…”
Section: Pharmacological Applications Of N-acyl Benzotriazolesmentioning
confidence: 99%
“…1d,129 In addition to the versatile synthetic utilities of N-acylbenzotriazoles, this scaffold possesses some notable bioactivities and explored in medicinal chemistry. 130 The structures of some biologically potent Nacylbenzotriazoles are depicted in Figure 3. For example, Nacyl/aroylbenzotriazoles 291 (IC 50 = 1.7 nM) and 292 (IC 50 = 14 nM) with 3,4,5-trimethoxy-substitution exhibited potent activities against oral epidermoid carcinoma KB cells, non-small-cell lung carcinoma H460 cells, and stomach carcinoma MKN45 cells with respect to doxorubicin.…”
Section: Review Synopen 5 Pharmacological Applications Of N-acylbenzo...mentioning
confidence: 99%
“…1,2,3-Benzotriazoles are an important class of heterocycles that have found widespread applications in organic synthesis, medicinal chemistry, and material science [ 9 , 10 , 11 , 12 , 13 ]. Historically, it has been reported that some 1-substituted 1,2,3-benzotriazoles could undergo denitrogenative transformations to generate other valuable products.…”
Section: Introductionmentioning
confidence: 99%
“…21 Benzotriazole-based compounds are a distinctive group of nitrogen-containing heterocycles that have garnered considerable interest among medicinal chemists. They are recognized as a promising class of bioactive heterocyclic product with diverse biological properties, 22 such as anti-inflammatory, 23 antiprotozoal, 24 antiproliferative, 25 anticancer, 26 antiviral, 27 plant growth regulatory 28 and antibacterial activities, 29 as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%